Menakar Urgensi dan Masa Depan Legislasi Fiqih Produk Halal di Indonesia - Rohmah, Siti; Tohari, Ilham; Kholish, Moh. Anas (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This article aims to identify and analyze the urgency and future of fiqh legislation for halal products in Indonesia. In addition, this article also aims to identify and analyze whether Law no. 33 of 2014 concerning the Guarantee of Halal Products is the result of authoritarianism in the name of Islamic law in Indonesia or is a constitutional guarantee for the majority of Muslims. The conclusion of this study shows that the effort to enact the jurisprudence of halal products through the Halal Product Guarantee Law is a constitutional necessity for Indonesian citizens who are predominantly Muslim. The regulation of halal certification in the Halal Product Guarantee Law is a form of legal certainty and constitutional protections for the majority of Muslims as consumers in Indonesia. In addition, the existence of the Halal Product Guarantee Law is also considered to provide benefits economically, socially, and healthily, which applies universally regardless of religion. Even the accusation that the Halal Product Guarantee Law is a product of authoritarianism that harms non-Muslims cannot be justified. Because the producers of food and medicine that are widely circulating in supermarkets and mini-markets in Indonesia are actually non-Muslim owners. Even with this halal certification, their products can enter the world market, especially in Muslim countries.